2019
DOI: 10.1103/physrevb.99.174511
|View full text |Cite
|
Sign up to set email alerts
|

Full proximity treatment of topological superconductors in Josephson-junction architectures

Abstract: Experiments on planar Josephson-junction architectures have recently been shown to provide an alternative way of creating topological superconductors hosting accessible Majorana modes. These zero-energy modes can be found at the ends of a one-dimensional channel in the junction of a twodimensional electron gas (2DEG) proximitized by two spatially separated superconductors. The channel, which is below the break between the superconductors, is not in direct contact with the superconducting leads, so that proximi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 87 publications
(112 reference statements)
1
12
0
Order By: Relevance
“…Previous investigations 37,39,42 have shown the im- portance of properly tuning the chemical potential, magnetic field strength, and superconducting phase difference for driving the JJ into the TS state. However, the strong dependence of the TS state and the ground-state phase on the spin-orbit angle (θ so ), the magnetic field orientation (ϕ B ), and the supercurrent direction (θ c ), shown in Fig.…”
Section: B Effects Of Crystalline Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations 37,39,42 have shown the im- portance of properly tuning the chemical potential, magnetic field strength, and superconducting phase difference for driving the JJ into the TS state. However, the strong dependence of the TS state and the ground-state phase on the spin-orbit angle (θ so ), the magnetic field orientation (ϕ B ), and the supercurrent direction (θ c ), shown in Fig.…”
Section: B Effects Of Crystalline Anisotropymentioning
confidence: 99%
“…In a more general scenario, there are situations in which the topological transition occurs without the current having a local minimum. 39,100 Figure 2(a) reveals that the topological gap is sizable only on a reduced part of the topological region. The topological gap is crucial for ensuring the practical protection of the MBS.…”
Section: Topological Superconductivity In Phase-unbiased Josephson Ju...mentioning
confidence: 99%
“…Current strategies explore the manipulation of Majorana zero modes (MZMs) in devices which rely on 1-D topological superconductivity [16][17][18][19] induced by the proximity effect in topological insulators or semiconductors with strong spin-orbit coupling, or via planar Josephson Junctions 20,21 . However, MZMs may be corrupted by non-topological low energy Andreev bound states (ABS) 22 , which can be present as a result of details of interfaces and materials properties in such systems 23 . Here we report the fragility of surface ABS in superfluid 3 He at an ideal non-transparent interface, exploiting the ability to tune in situ the scattering of quasiparticles by the surface through adjustment of the isotopic composition of the helium surface boundary layer.…”
mentioning
confidence: 99%
“…Furthermore, it has also been shown that the presence of critical current minima may not necessarily be associated to transitions between the trivial and TS states [45] and a further analysis of magnetic and crystalline anisotropies of the TS state [46,47] may be needed to better understand the physical origin of the critical current minima [36]. In spite of the challenges, planar JJs continue to attract attention due to their experimental feasibility, versatility, and enhanced region of system parameters supporting the TS state [41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…Therefore, although in some cases the ground-state phase jumps appear to occur at the same Zeeman energy at which the critical current minima occur, this is, in general, not necessarily true. Further, the existence of ground-state jumps may not even be accompanied by critical current minima (nor vice versa), especially for junctions with narrow S regions [49]. In such cases, the existence of current minima does not necessarily represent a signature of topological phase transition.…”
mentioning
confidence: 99%